Sensitivitas dan Keragaan Tanaman Coleus sp. terhadap Mutasi Induksi Kimia Menggunakan Ethyl Methane Sulfonate (EMS) Aplikasi Cara Rendam dan Tetes - Sari, Dia Novita; Aisyah, Syarifah Iis; Damanik, dan Muhammad Rizal Martua (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Variant of Coleus sp. in Indonesia is very low. Induced mutation by Ethyl Methane Sulphonate (EMS) is able to increase variant of Coleus sp.. EMS is a mutagen that is effective and efficient in causing mutations. In mutation breeding, the high variant usually occurs around LC50 (Lethal Concentration). The objective of this study were (1) to obtain the LC50 value and sensivity of coleus plants, and (2) to evaluate the response of plant growth and to obtain new variance of coleus used soak and drops by EMS application. The experiment was arranged in randomized complete block design with three replications in each coleus. The materials used two Coleus sp. shoot cuttings i.e., C. amboinicus Lour. and C. blumei the purple/green color and the red. The concentration of EMS consisted of 0.00, 0.50, 0.75, 1.00, and 1.25% with application soak method (100 minutes) and drops (3 drops pipette). The results showed that the LC50 value of C. amboinicus Lour. 5.86% (soak). The LC50 value of C. blumei the purple/green color was 0.69% (soak), 0.82% (drops) and the red color 0.29% (drops), 0.89% (drops). C. blumei (the purple/green and red) was higher sensitivity rather than C. amboinicus Lour. There was an interaction between treatments on C. amboinicus Lour. whereas C. blumei (purple/green and red) had no interaction among treatments. C. amboinicus Lour. produced one putative mutant and C. blumei purple/green produced four putative mutants based on the morphology.Keywords: Coleus amboinicus Lour., Coleus blumei, LC50, putative mutan